2022
DOI: 10.1021/acscatal.2c02429
|View full text |Cite
|
Sign up to set email alerts
|

C(sp2)–H Activation with Bis(silylene)pyridine Cobalt(III) Complexes: Catalytic Hydrogen Isotope Exchange of Sterically Hindered C–H Bonds

Abstract: The bis­(silylene)­pyridine cobalt­(III) dihydride boryl, trans-[ ptol SiNSi]­Co­(H)2BPin ( ptol SiNSi = 2,6-[EtNSi­(NtBu)2CAr]2 C5H3N, where ptol = 4-MeC6H4, and Pin = pinacolato) has been used as a precatalyst for the hydrogen isotope exchange (HIE) of arenes and heteroarenes using benzene-d 6 as the deuterium source. Use of D2 as the source of the isotope produced modest levels of deuterium incorporation, and stoichiometric studies established modification of the pincer ligand through irreversible addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Transition-metal-catalyzed hydrogen isotope exchange (HIE) provides efficient methodologies for the incorporation of deuterium atoms into small molecules, but it is challenging to control the quantity and precise site of deuterium atoms . Notably, an excess of deuterium reagent is required for this approach to guarantee a high level of deuterium incorporation in a given molecule …”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-catalyzed hydrogen isotope exchange (HIE) provides efficient methodologies for the incorporation of deuterium atoms into small molecules, but it is challenging to control the quantity and precise site of deuterium atoms . Notably, an excess of deuterium reagent is required for this approach to guarantee a high level of deuterium incorporation in a given molecule …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the C–H activation of these challenging positions would enable Pd-catalyzed homogeneous sp 2 C–H perdeuteration for the preparation of perdeuterated drug molecules that are key to drug discovery . Therefore, to complement currently available homogeneous catalytic protocols, , mild and functional-group-compatible methods using readily available ligands and deuterium sources would be highly desirable . In addition, selective alkenylation at the less-electron-rich positions over the conventionally more reactive electron-rich positions of arenes would offer the possibility to perform regiodivergent alkenylation .…”
Section: Introductionmentioning
confidence: 99%
“…[15b,c] With the development of new NHSi ligands, bis(silylene)cobalt complexes have been found application in several catalytic transformations including [2 + 2 + 2] cycloaddition of phenylacetylene, [16] borylation of arenes, and hydrogen isotope exchange of arenes and heteroarenes. [17] To our knowledge, hydrogenation of olefins catalyzed by cobalt complexes with NHSis has remained unknown. Herein, we report the results of highly chemo-selective hydrogenation of alkenes by a structurally well-defined Co(I) complex with a strong electron-donating NHSi ligand.…”
Section: Introductionmentioning
confidence: 99%
“…found that a bis( N ‐heterocyclic silylene)xanthene nickel(0) complex is an efficient precatalyst for hydrogenation of olefins, in which the nickel‐silylene cooperation is essential in the catalytic process [15b,c] . With the development of new NHSi ligands, bis(silylene)cobalt complexes have been found application in several catalytic transformations including [2+2+2] cycloaddition of phenylacetylene, [16] borylation of arenes, and hydrogen isotope exchange of arenes and heteroarenes [17] . To our knowledge, hydrogenation of olefins catalyzed by cobalt complexes with NHSis has remained unknown.…”
Section: Introductionmentioning
confidence: 99%